Feasibility and impact of a 1-minute daily functional exercise regimen prescribed to older adults by their primary care physician - Sciamanna, Christopher N. (Prev Med Rep, 2021)
Despite the inverse relationship between physical activity (PA) and physical function, few older adults achieve PA recommendations. In response to observations that “lack of time” underlies reduced PA among older adults, recent work suggests even short bouts of PA can improve health and fitness. In addition, because they are frequently visited by older adults, an important conduit for PA promotion could be the primary care physician (PCP). However, most PCPs receive little training related to PA, rendering it difficult for them to offer meaningful counseling. Therefore, we explored the feasibility and impact of a PCP-prescribed one-minute daily functional exercise program, consisting of 30 s each of bodyweight push-ups and squats, among 24 patients 60 years of age or older. 42% of patients who were contacted started the exercise prescription and, over 24-weeks, completed approximately 114 sessions, while 75% completed at least half of the possible daily exercise sessions. As a group, the patients demonstrated increases in both maximal push-up and squat performance, though these increases plateaued following week-12. These preliminary results suggest that a PCP prescription of one-minute of daily functional exercise among older adult patients was feasible, acceptable, and effective for improving functional physical fitness. Given these findings, formal controlled research with recruitment from multiple clinics, random assignment to treatment conditions, and blinded assessments of objective functional physical performance should be pursued.